2009
DOI: 10.1007/s10661-009-1129-9
|View full text |Cite
|
Sign up to set email alerts
|

Trihalomethane formation potential in treated water supplies in urban metro city

Abstract: Trihalomethane (THM) formation potential (TFP) is very useful test to assess the level of the formation of trihalomethanes in worst case scenario. Organics in water have the potential to generate harmful disinfection by-products (DBPs) such as THMs, as a result of their reaction with disinfectant chlorine used in drinking water. DBPs are increasingly recognized as cancerous agents. TFP of postchlorinated treated water were investigated at six water treatment plants (WTPs) in Delhi City (India). The present pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…(Sketchell et al 1995, Chellam 2000, Elshorbagy et al 2000, Chaib and Moschandreas 2006, Shmeis et al 2009, Hasan et al 2010, Platikanov et al 2010. pH, temperature, inorganic ion (particularly bromide) concentration], and chlorination conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…(Sketchell et al 1995, Chellam 2000, Elshorbagy et al 2000, Chaib and Moschandreas 2006, Shmeis et al 2009, Hasan et al 2010, Platikanov et al 2010. pH, temperature, inorganic ion (particularly bromide) concentration], and chlorination conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In different geographical locations, such as Spain, China, South Korea, Greece, the US, and Iran, the average THMs in WTP vary widely, namely, 9-177 mg/L and sometimes exceeding regulatory limits (Krasner & Wright 2005;Platikanov et al 2012;Hladik et al 2014;Ramavandi et al 2015). Particularly in tropical regions, research focus to examine the effects of waterworks' management practices on THM formation are limited (Abdullah et al 2003;Panyapinyopol et al 2005;Baytak et al 2008;Hasan et al 2010;Amjad et al 2013). None of these studies specifically assessed the effects of different treatment technologies on THM formation.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have revealed that THM formation is very complex since it can be affected by several factors including concentration and natural organic matter (NOM) indicators such as specific ultraviolet absorbance (SUVA), total organic carbon (TOC), ultraviolet absorbance at 254 nm wavelength (UV 254 ), water quality parameters (e.g. pH, temperature, inorganic ion (particularly bromide) concentration), and chlorination conditions (e.g., contact time or travel time of water in the system, applied chlorine dose, chlorine residual) (Hasan et al, 2010;Sketchell et al, 1995;Chellam, 2000;Chaib and Moschandreas, 2006;Shmeis et al, 2009;Platikanov et al, 2010). In addition, due to the adverse health effects on humans, several treatment alternatives have been developed to achieve the removal of DBPs like THMs from drinking waters.…”
Section: Introductionmentioning
confidence: 99%
“…No previous attempts have been made to develop these models for prediction of TTHMs removal in Turkey. A few studies have focused on the determination of TTHM removal (Hasan et al, 2010;Mishra et al, 2012). In this study, the models were developed against an individual dataset of THM measurements in water samples taken from September 2014 to May 2015 in the same reservoir waters and chlorinated under identical conditions.…”
Section: Introductionmentioning
confidence: 99%